THE PORTRAYAL OF MEERICK ROCHA’S LONELINESS IN “TAKEN” BY KELLIE MAINE - Mochamad Kriswandi; Erika Citra Sari Hartanto (Universitas 17 Agustus 1945 Surabaya, 2022)
The purpose of this study was to discover The Portrayal of Merrick Rocha’s Loneliness in “Taken” by Kellie Maine using Psychological Approach. The loneliness issue and its impacts were able to be perceived by discovering the reasons and the impacts of loneliness. Qualitative research was held in this study. The result of this study showed that the writer could find four reasons of Merrick Rocha’s loneliness and three positive ways to reduce his loneliness inside Taken by Kelli Maine. Those four reasons behind Merrick Rocha’s loneliness are (1) Being Unattached, (2) Alienation, (3) Being Alone, and (4) Dislocation. For the ways or impacts of loneliness, this study found three positive impacts such as (1) Active Solitude, (2) Distraction by Spending Money, (3) Active Solitude. The negative one (4) Sad Passivity does not exist in the novel because Merrick Rocha’s loneliness